Awareness of health risks associated with smokeless tobacco use among users in Pretoria - Tombo Bongongo; Yusuf Jeewa; Doudou K. Nzaumvila; Indiran Govender (South African Family Practice)
Background: Smokeless tobacco (ST) refers to all tobacco-containing products that are not smoked but rather consumed through other means. Contrary to the popular belief that ST products are safe, the use of such products exposes users to health risks. To assess the awareness of health risks associated with ST use among users in a Pretoria community, the study was conducted in Ramotse community, located in Tshwane region 2, Gauteng, South Africa.